Links between employment-related factors and physical and mental health among uninsured expatriate males in Saudi Arabia - Alkhamis, Abdulwahab A.; Miraj, Shaima S. Ali (International Journal of Health Sciences, 2018)
Objectives: The objectives were to determine whether employment-related factors had influence on physical and mental health outcomes among uninsured expatriates working in Saudi Arabia and to identify whether these factors act as facilitators or barriers to health. Methods: Cross-sectional face-to-face interviews using previously published methods were conducted among a multi-stage stratified cluster sample of 1370 employees as their problems in seeking health benefits have not been studied. Male expatriates working in different companies representing several trades in Riyadh were selected for which tested questionnaires were administered to them. Results: Among 1370 uninsured expatriates, across various tested independent variables, age and income level were having most prominent influences on self-rated perceptions of physical and mental health. Uninsured expatriates with 60 plus age group have 71% more chances of detiorating physical and mental health as compared to their younger age group uninsured expatriates. The expatriates earning less than SR 2000 had 68% more chances of having poor physical and mental health as compared to their counterparts earning more than SR 6000, indicating more adverse outcomes among people in low income categories. 74% of the expatriates having maximum education were found to have better physical and emotional outcomes than the less educated ones. Conclusion: The present study provides useful insights into the complex healthcare system in Saudi Arabia and contributes to the exploration of health behaviours and the shaping of health perceptions among expatriates.